Evaluating the Inﬂuence of Tutors’ Digital Assessment-Related Knowledge on Assessment Practices in Higher Education - Dadzie, Justice; Ezugwu, Ifesinachi Jude; Kpodoe, Ivy Ama; Anhwere, Daniel Kweku; Oppong, Frank; Oyeniran, Daniel (International Journal of African Higher Education, 2025)
This research study investigates the inﬂuence of tutors’ digital assessment pedagogical knowledge on various assessment practices, including automated, continuous, responsible, and authentic assessments. The results indicate that Digital Assessment Pedagogical Knowledge (DA_PK) has a signifcant inﬂuence on Automated Assessment (R2 = 0.823) and Continuous Assessment (R2 = 0.753), highlighting the importance of tutors’ profciency in digital assessment practices for enhancing student learning experiences. Additionally, the fndings reveal that Digital Assessment Pedagogical Content Knowledge (DA-PCK) explains 93% of the variation in Continuous Assessment and 34.1% of the variation in Automated Assessment, emphasizing the critical role of integrating technology, pedagogy, and content expertise in shaping eﬀective assessment strategies. Furthermore, Digital Assessment Technological Pedagogical Knowledge (DA-TPK) demonstrates a remarkable inﬂuence, accounting for 96.5% of the variation in responsible assessment and 43.4% of the variation in continuous assessment, underscoring the signifcance of tutors’ technological and pedagogical knowledge in fostering ethical, accountable, and continuous assessment practices.